MaUGT79 confers drought tolerance by regulating scopolin biosynthesis in plants - Duan, Z.; Wu, F.; Yan, Q.; Wang, S.; Wang, Y.; Xie, Z.; Li, M.; Jones, Christopher S.; Zhou, P.; Zhang, C.; Zhang, J. (Wiley, 2025)
The coumarin scopoletin and its glycosylated form scopolin constitute a vast class of natural products that are considered to be high-value compounds, distributed widely in the plant kingdom; they help plants adapt to environmental stresses. However, the underlying molecular mechanism of how scopolin is involved in the regulation of plant drought tolerance remains largely unexplored. Here, UDP-glycosyltransferase 79 (MaUGT79) was genetically mapped as the target gene by bulk segregant analysis sequencing (BSA-seq) from two Melilotus albus near-isogenic lines (NILs). MaUGT79 exhibits glucosyltransferase activity toward scopoletin. The expression of MaUGT79 is induced by drought stress, and it was found to mediate scopolin accumulation and reactive oxygen species (ROS) scavenging under drought stress. Moreover, MaMYB4 transcriptionally upregulated MaUGT79 was also verified to be involved in modulating scopolin biosynthesis and improving plant drought tolerance. Collectively, this study demonstrates that MaMYB4 enhances drought tolerance through activating MaUGT79 expression and promoting scopolin biosynthesis. While MaUGT79 represents a key target of MaMYB4-mediated scopolin biosynthesis and drought adaptation, the potential involvement of additional regulatory pathways warrants further investigation. These findings provide important insights into how scopolin accumulation may contribute to plant adaptation to environmental stresses.